Changes in hospital admissions and inpatient tariff associated with a Diabetes Integrated Care Initiative: Preliminary findings (与糖尿病综合护理计划相关的住院以及住院费用的变化：初步调查结果). (30th July 2013) - Simmons, David; Yu, Dahai; Wenzel, Helmut
Abstract Background The Diabetes Integrated Care Initiative (DICI) has tested whether hospital admissions and total amounts paid for inpatient care have declined through closer (integrated) working between primary, secondary and community diabetes services in Cambridgeshire. Method Poisson regression models were used to compare the percentage change in hospital admissions, and tariff paid, before and after each of 43 months (April 2007 – November 2010). East Cambridgeshire and Fenland (ECF) practices were divided into those fully (n = 10) and less (n = 7) "engaged" with the intervention defined by the extent of their uptake of intervention components between July 2009 and June 2010. Other parts of the county were "controls". Results Among patients with diabetes in the fully engaged ECF practices, the monthly average hospital admission rate was 19.0% (13.9, 24.2) higher (7.7 hospital admissions per 1000 patients) and the monthly tariff paid was 28.8% (28.7, 28.9) higher (£19.60 per patient per month), at the time of introducing the DICI versus the pre‐implementation period (April 2007 to June 2009). These differences, had dropped to 8.7% (1.9, 15.6) and 13.4% (13.2, 13.5) (£9.92 per patient per month) higher 12 months after introduction. Comparable reductions in the rate of increase were not seen among those without diabetes or in control areas. Conclusion During the DICI, patients with diabetes from "fully engaged" practices experienced increased hospitalization and amount paid for in‐patient care, the extent of which trended downwards by 12 months. Further time is needed to monitor whether this trend is sustained.